2003
DOI: 10.1002/glia.10305
|View full text |Cite
|
Sign up to set email alerts
|

Selective staining by vital dyes of Müller glial cells in retinal wholemounts

Abstract: Müller glial cells within the retina may respond to different signaling molecules with an elevation of their intracellular free calcium. To prove the localization of the recorded calcium responses in Müller cells within acutely isolated retinal wholemounts, retinal pieces from adult animals and humans were exposed to different vital dyes just after the calcium imaging records were finished. The dyes, Mitotracker Orange, Mitotracker Green, Celltracker Orange, Celltracker Green, and monochlorobimane, are all sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 15 publications
4
51
0
1
Order By: Relevance
“…They were capable of selective uptake of vital dyes (Fig. 2 b-g) (20,21) and could be counterstained with an antibody directed against vimentin ( Fig. 2 f and g).…”
Section: Resultsmentioning
confidence: 99%
“…They were capable of selective uptake of vital dyes (Fig. 2 b-g) (20,21) and could be counterstained with an antibody directed against vimentin ( Fig. 2 f and g).…”
Section: Resultsmentioning
confidence: 99%
“…All experiments were performed at room temperature (20 -23°C). Retinal slices or isolated cells were loaded with the vital dye Mitotracker Orange (10 M), which has been shown to stain somata of Müller glial cells selectively in the inner nuclear layer of retinal tissues (41). After an incubation time of 3 min, slices or cells were continuously perfused with extracellular solution at a flow rate of 2 ml/min, and recordings were made with an Achroplan 63ϫ/0.9 water im-mersion objective.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that Mitotracker Orange is taken up selectively by Mü ller glial cells in the retina, whereas neurons remain unstained. 29 The dye was dissolved in extracellular solution that contained 136 mmol/L NaCl, 3 mmol/L KCl, 2 mmol/L CaCl 2 , 1 mmol/L MgCl 2 , 10 mmol/L HEPES-Tris, and 11 mmol/L glucose, pH 7.4. A gravity-fed system with multiple reservoirs was used to perfuse the recording chamber continuously with extracellular solutions; the hypotonic solution was added by fast changing of the perfusate.…”
Section: Mü Ller Cell Swellingmentioning
confidence: 99%